DAMPAK MANAGEMEN PADA RANTAI PASOK TERHADAP KINERJA KEBERLANJUTAN EKONOMI, KINERJA KELESTARIAN LINGKUNGAN DAN KINERJA KEBERLANJUTAN SOSIAL PT KRAKATAU STEEL (PERSERO) TBK - Kurniawan, Dana Rizky; Mahestri, Nabila Anibka; Maylawati, Windi; Rustandi, Tata (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
In the last decades, several environmental problems have increased. Therefore, many companies are currently paying attention to environmental issues. Attention is not only to the production process but to all activities including maintaining a green pattern in every construction activity. This research uses the Green Supply Chain Operation Reference method to evaluate the performance of green supply chain management in steel companies. This research aims to determine the factors that influence productivitylevels and improvement efforts by considering environmental performance indicators. The main activities that come out of the literature are: green operations, green design, green manufacturing, logistics flows, and waste management. The discussion also covers key drivers of green initiatives including government compliance, customer improvement and community relations. Innovations implemented in the future are able to result in business improvements for the Company through predetermined stages.